Drumontiana zhilini sp. nov., a new species from Guangxi, China (Coleoptera: Cerambycidae: Prioninae) - Wang, Ying-Qi; Wang, Ping; Xie, Guang-Lin; Wang, Wen-Kai (Zootaxa, 2024)
In this work, a new species of the genus Drumontiana Danilevsky, 2001 (Cerambycidae: Prioninae) is described and illustrated, namely Drumontiana zhilini sp. nov. from Huaping National Nature Reserve, Guangxi, China.